National Conference on Inclusive Development through Biotechnology: Life Sciences-Biotechnology - DR. ESTHER SHOBA R, Convener (International Journal of Life Science and Pharma Research, 2020)
Biotechnology is at the forefront of the battle, to improve the lives of millions throughout the world – by improving agricultural yields and food security, by developing alternative fuels. It has revolutionized mankind since its existence. It provides effective diagnostics, prevention and treatment measures including production of novel drugs and recombinant vaccines.